PELATIHAN PENGGUNAAN CHATBOT UNTUK PEMASARAN PRODUK UMKM KADIN KOTA BANDUNG - Yenny Maya Dora; Sunardi Sembiring Brahmana; Nugraha Saefudin; Uce Karna Suganda; Raden Mochamad Daud Rizky F (LPPM Universitas Nusa Mandiri, 2026)
The rapid development of digital technology provides opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their marketing reach and improve customer service quality. However, many MSMEs still face challenges in utilizing digital technology effectively for marketing and customer communication. According to the MSME Empowerment Report (2022), approximately 70.2% of MSMEs experience difficulties in marketing their products, particularly in developing effective digital marketing strategies and providing responsive customer service. Therefore, this community service program aimed to improve the knowledge, understanding, and skills of MSMEs assisted by the Bandung City Chamber of Commerce and Industry (KADIN) in utilizing chatbot applications for digital marketing and customer service. The program involved 20 MSME participants and was conducted through lectures, discussions, and hands-on practice using chatbot applications. Evaluation was carried out using questionnaires to measure participants' understanding and satisfaction with the training. The results showed that 100% of participants stated that the program was well organized, 95% agreed that the implementation followed the planned schedule, and 100% reported that the training materials were easy to understand and that the facilitators answered participants' questions clearly. In addition, participants were able to create chatbot accounts, utilize auto-reply features, and develop automated responses to customer inquiries. These findings indicate that chatbot training can improve MSMEs' knowledge, understanding, and skills in utilizing digital technology to support marketing activities and enhance customer service quality.